Institutional arrangements to make public spending responsive to the poor: When intent meets political economy realities - Mogues, Tewodaj; Erman, Alvina (Wiley, 2020)
Researchers and practitioners increasingly appreciate that accounting for the needs of ordinary citizens in developing countries supports the process of pro‐poor public resource allocation.We examine the existing evidence with regard to four institutional arrangements that endeavour to make public spending responsive to the needs of the poor by moving decision‐making procedures closer to the population. We term these “responsive institutional arrangements” (RIAs).We scrutinize the evidence in the literature on the functioning of each RIA against a framework that considers how countries’ broader governance environment shape governments’ incentives.The article concludes that RIAs can channel resources based on the preferences of the poor, but mainly if citizens have political space, and governments the incentives, to allocate resources in a pro‐poor fashion. Otherwise, RIAs often become tools of control for elites. However, the evidence suggests that higher inequality has an eroding effect on the functionality of RIAs. We argue that past optimism toward RIAs should be replaced by a more refined understanding.Policy implications include that RIAs can especially be fostered where there is a pre‐existing strong civil society, and political accountability. Achievable RIA improvement targets incentivize local government leaders to be responsive to ordinary individuals.